2001
DOI: 10.1128/cdli.8.3.616-623.2001
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Complement Source in Measuring Meningococcal Bactericidal Titers

Abstract: Complement-mediated bactericidal antibodies in serum confer protection against meningococcal disease. The minimum protective titer is estimated to be between 1:4 and 1:8 when measured by the Goldschneider assay performed with human complement, the assay used in the 1960s to establish the correlation between bactericidal antibodies and protection. A more recently described bactericidal assay standardized by an international consortium uses rabbit complement, which is known to augment bactericidal titers. To def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 19 publications
5
73
2
2
Order By: Relevance
“…12 Previous studies have found a lack of correlation between hSBA and rSBA results; 12 however, our data did not detect any instances where the rSBA results contradicted the hSBA results. For serogroups A, W-135 and Y, MenACWY-CRM recipients were significantly more likely than MCV4 recipients to have evidence of bactericidal antibodies almost 2 years after vaccination, regardless of the complement source used, while the proportions of subjects achieving rSBA or hSBA titers ≥8 were similar for serogroup C in recipients of both vaccines.…”
Section: Discussioncontrasting
confidence: 80%
“…12 Previous studies have found a lack of correlation between hSBA and rSBA results; 12 however, our data did not detect any instances where the rSBA results contradicted the hSBA results. For serogroups A, W-135 and Y, MenACWY-CRM recipients were significantly more likely than MCV4 recipients to have evidence of bactericidal antibodies almost 2 years after vaccination, regardless of the complement source used, while the proportions of subjects achieving rSBA or hSBA titers ≥8 were similar for serogroup C in recipients of both vaccines.…”
Section: Discussioncontrasting
confidence: 80%
“…34,51,66 The titers of bactericidal activity were between 1:8 and 1:16, surpassing the accepted values for protective bactericidal activity titers in Europe ( 1:4) and in the US ( 1:8). 67 In summary, these data support the use of rPorA as an adjuvant and in the development of a novel meningococcal B oral vaccine. The next-generation vaccine NonaMen induced high SBA titers against all tested MenB strains, when administered subcutaneously in rabbits and mice, regardless of whether aluminum phosphate was used as an adjuvant, 31 suggesting that an adjuvant was not necessary.…”
Section: Discussionsupporting
confidence: 53%
“…Serum bactericidal activity also was measured with internal human complement, which was used in the Goldschneider et al study (10), or exogenous rabbit complement, which because of ease of standardization is currently used by most laboratories to measure bactericidal titers (1, 3) but is known to give higher bactericidal titers than human complement (3,32). Irrespective of the source of complement used, protective activity was more frequently found in sera that were positive for bactericidal activity (with a titer of Ն1:4 with human complement or Ն1:128 with rabbit complement) than in sera that were negative for bactericidal activity (P Ͻ 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…For log transformation, samples below the lower limits of detection were assigned a value of half of the lower limit (i.e., 1:2 for the bactericidal titer and 0.05 g/ml for group C anticapsular antibody concentration measured by RABA). The proportion of sera with bactericidal titers of Ն1:4 (considered a protective titer [10]) or Ն1:128 when measured with rabbit complement (a titer previously shown to predict a bactericidal titer of Ն1:4 when measured with human complement [32]) was computed. Differences found in the proportion of subjects in the respective groups were compared by chi-square analysis.…”
Section: Serum Samplesmentioning
confidence: 99%
See 1 more Smart Citation